#TITLE_ALTERNATIVE# - BAPTISTA (NIM 12306063) pembimbing : Dr. Hendra Grandis ; Dr. Djedi S. Widarto, YOHANES
In order to obtain a better result in studying the subsurface geology condition of ”YR” Block, gravity data acquisition has been done after the seismic data acquisition. Processed seismic data give poor resolution for layers below the pre–salt so that the determination of its basement configuration could not be done well. Gravity data processing was done in order to support the determination of basement configuration by filtering using moving average method in two steps. The first filtering using filter window 9 (8x8 km) yields shallow residual anomaly, with its average unconformity contact at about 1,100 m depth. The second filtering using filter window 21 (20x20) yields deeper residual anomaly, with its average unconformity contact at about 3,878 m depth. From the residual anomaly map using window 21, early interpretation indicates the existence of fault structures above the basement. From gravity modellings it can be interpreted that the basement topography is relatively more flat to the south. Low anomaly values can be caused by either thick amount of salt or the deeper basement elevation and vice versa.